2011
DOI: 10.1175/jtech-d-10-05030.1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Lag Correction on Slocum CTD Glider Data

Abstract: In this work a new methodology is proposed to correct the thermal lag error in data from unpumped CTD sensors installed on Slocum gliders. The advantage of the new approach is twofold: first, it takes into account the variable speed of the glider; and second, it can be applied to CTD profiles from an autonomous platform either with or without a reference cast. The proposed methodology finds values for four correction parameters that minimize the area between two temperature-salinity curves given by two CTD pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
143
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(143 citation statements)
references
References 7 publications
(12 reference statements)
0
143
0
Order By: Relevance
“…The derivation of the salinities generally followed the procedure described by Garau et al (2011). They showed that applying a glider-speed-dependent delay to the temperature allowed for the calculation of optimal, i.e.…”
Section: Glider Surveymentioning
confidence: 99%
“…The derivation of the salinities generally followed the procedure described by Garau et al (2011). They showed that applying a glider-speed-dependent delay to the temperature allowed for the calculation of optimal, i.e.…”
Section: Glider Surveymentioning
confidence: 99%
“…In this paper, we describe the processing procedures that we have developed for improving the accuracy of salinity derived from the UCTD. The results are also likely to be useful for other applications in which unpumped CTD measurements are made, for example, autonomous gliders (Garau et al 2011) or the Moving Vessel Profiler (Furlong et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Glider variables have been processed using an opensource MATLAB-based toolbox (https://bitbucket.org/ bastienqueste/uea-seaglider-toolbox/) in order to correct for differing timestamp allocations, sensor lags (Garau et al, 2011;Bittig et al, 2014), and to tune the hydrodynamical flight model (Frajka-Williams et al, 2011). Outliers outside of a specified range (e.g.…”
Section: Glider Sensorsmentioning
confidence: 99%